Reliability of selected performance analysis systems in football and rugby - James, N.; Jones, N. M. P.; Hollely, C. (4th International Conference on Methods and Techniques in Behavioral Research, 27-30 August 2002, 2002)
In this study, operational definitions of behaviors were formulated and configurations set up using The Observer. Once the two configurations were complete, matches were coded. The adaptability of The Observer meant that configurations and operational definitions could be amended match by match, as the need arose. This took eight matches for rugby, where 38 anomalies occurred (79% were operational definitions, 13% configuration changes and 8% remained irresolvable), but only two matches for football, where all 9 changes involved the configuration. This difference was largely due to the rugby configuration being used to provide weekly feedback to a professional team, whereas the football configuration was used solely for research purposes. Hence, there was more time pressure to complete the rugby configuration, resulting in less robust operational definitions than for the football. The unique difficulties in observing behaviors in each sport would have also contributed to other errors, however.